The Mechanism of Decline of Senescent Skeletal Muscle Satellite Cell Self-Renewal and Regenerative Proliferation: The Role of Heparan Sulfate-FGF-2--FGFR1-p38αMAPK Axis, Sprouty1, miR-1, miR-133 and miR-29a - Papaconstantinou, John (Journal of Skeletal Muscle, 2020)
Aging mammalian skeletal muscle satellite cells (MuSCs) undergo a decline of stem cell/progenitor cell proliferative and regenerative capacity, and the development of a physiological milieu characteristic of a state of chronic sterile inflammation. p38αMAPK and ERK1/2 are two major signaling pathways that regulate the age-associated decline of MuSC proliferative capacity. In this review we propose the following mechanism that links the p38αMAPK pathway to the decline of self-renewal and regenerative capacity of aged MuSCs: a) the HS-FGF-2-FGFR1-p38αMAPK-Axis, a tightly linked homeostatic signaling complex, is in synchrony with the autoinhibition of FGFR1; b) autoinhibition contributes to the Axis’ regulation of the homeostasis of P-p38αMAPK activity in juvenile MuSC; c) this combination of protein-protein interactions is characteristic of a juvenile cytoplasmic milieu of beneficial P-p38αMAPK activity and d) includes Sprouty1 inhibition that supports the stimulation of FGF-2 --> miR-29a; e) the miR29a dismantles the basement membrane in preparation for the initiation of replication; f) an age-associated impaired, dysregulated, over-sulfated heparan sulfate ligand (HS)-FGF-2 fails to activate FGFR1 in aged MuSCs; g) this uncouples its regulation of p38αMAPK and ERK1/2 pathways and results in desensitization of FGFR1; h) desensitization of FGFR1 and Sprouty1 interaction in aged MuSC uncouples their regulation of P-p38αMAPK in the aged MuSCs; i) this enables a state of chronic sterile inflammation to promote and sustain an increased level of P-p38αMAPK activity; and, j) the increased activity of P-p38αMAPK in aged MuSC stimulates the production of cell cycle inhibitors, miR-1 and miR-133, thereby attenuating the expression of the cell cycle regulators, SP1 and cyclin D1, resulting in a G1/S arrest; j) the increased level of p38αMAPK activity promotes the apoptosis of the aged activated MuSCs. This mechanism involves the synergistic interactions of HS-FGF2-FGFR-1, Sprouty (spry1), miR-1, miR-133 and miR-29a that unify the extracellular niche and intracellular milieu for the juvenile vs age-associated regulation of proliferative capacity of the MuSC. Our hypothesis unifies these interactions with the role of the extracellular niche and intracellular milieu in the stimulation of juvenile proliferation vs age-associated decline of skeletal muscle satellite cell self-renewal and regenerative proliferation. Word Count = 344
Keywords: Skeletal Muscle Satellite Cells; Self-Renewal; p38αMAPK; Sprouty1; miR-29a